Persons meet nature : a kantian appraisal of Paul Taylor’s ethical worldview - Almeida, Domingos Paulo Ferreira de (2023)
In Respect for Nature (1986), Paul Taylor offers a comprehensive egalitarian and individualist biocentric ethical theory named ‘respect for nature’, grounded in a ‘biocentric outlook on nature’, in which moral worth belongs equality to all individual organisms. In addition, he propounds a human ethics of Kantian inspiration, ‘respect for persons’, for interpersonal moral relations, which served as a template for ‘respect for nature’. Exploring the structural correspondence between the two ethical theories, I show that the fundamental value concept of respect for nature, inherent worth, is incoherent in its deontological use. As a result, Taylor forces a major schism in the moral community separating moral relationships between persons in a Kantian kingdom of ends from the moral relations between persons and nonperson organisms. A second schism is further introduced in inherently worthy organisms to set aside the wild organisms in a moral community instituted by the theory of respect for nature, the Earth’s community of life. In construing the moral community that Taylor names ‘Earth’s community of life’ using his own assumptions regarding persons and the natural world, I conclude that a logocentric construction of the biotic moral realm is unavoidable; the Earth’s community of life is thus pictured as a kingdom of ends with a constitutional amendment that makes all living organisms moral subjects but irreducibly unequal to moral legislators. Taylor’s characterization of all organisms as teleological centers of life is explicated and protected against a number of objections as a productive account of organisms and a useful bridge between biology and morality. The claim that every organism has a unique point of view regarding its own life stands but, I suggest, ineliminable conceptual anthropocentrism limits human ability to assume their point of view across the spectrum of life. My assessment of Taylor’s biocentric outlook on nature leads to the rejection of biocentric egalitarianism but, with some caveats, preserves organismic life as a fundamental ethical category and the teleological stance regarding living organisms. Building upon my criticism of Taylor’s outlook on nature and resorting to Kant’s conception of reason, understanding, and the faculty of judgment, I advance a Taylor-inspired Kantian outlook on living organisms generalized to persons and nonpersons.